Heat capacity of mesoscopically disordered superconductors: implications for MgB2 - Gabovich, A. M.; Voitenko, A. I.; Li, Mai Suan; Szymczak, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The electronic specific heat C as a function of temperature T is calculated for a mesoscopically disordered s-wave superconductor treated as a spatial ensemble of domains with continuously varying superconducting properties. Each domain is characterized by a certain critical temperature Tc0 in the range [0,Tc] and is supposed to have a size L > x, where x is the coherence length. Specific calculations are performed for exponential and Gaussian distributions of Tc0. For low T, the spatially averaged áC(T)ñ is proportional to T2, whereas the anomaly at Tc is substantially smeared even for small dispersions. For narrow gap distributions there exists an intermediate T range, where the curve áC(T)ñ can be well approximated byan exponential Bardeen-Cooper-Schrieffer-like dependence with an effective gap smaller than the weak-coupling value. The results obtained successfully reproduce the salient features of the C(T) data for MgB2, where a wide superconducting gap distribution has been observed previously in the tunneling, point-contact, photoemission and Raman spectra. The conclusionis reached that the multiple-gap behavior of superconducting MgB2 is due to the spatial distribution of dissimilar domains. Intrinsic nonstoichiometry of the compound or possible electronic phase separation may be the origin of the mesoscopic inhomogeneities. The same modeldescribes the low-T heat capacity of cuprates, although the sources of inhomogeneity are different from those in MgB2.